Lektürekanon eines Fürstendieners die Privatbibliothek des Friedrich Rudolf von Canitz (1654-1699) - Lingnau, Anna (bibliothek altes Reich, 2021)
What should the servant to prince in the 17th century read? This question was of interest to scholars as well as princely servant themselves, such as the privy counsellor and envoy Friedrich Rudolf von Canitz (1654-1699). The aim of this study is to disclose the intellectual currents contained in his library. This is accomplished not only through traditional library analysis, but also, for the first time, through canon research